Prediction and Analysis of Operating Conditions of Industrial Methanol Synthesis Reactor Using Artificial Neural Network-Based Model - Izer, Abdullah Fahmi (Universiti Teknologi PETRONAS, 2016)
Methanol synthesis has many type of method that has been used these days for its process. The basic process was divided into two steps (Brooke Hays,2015). The first step was the conversion of feedstock, which is the natural gas to synthesis gas (CO, CO₂, H₂O, H₂). The second step involved the catalytic synthesis, where the process of converting the synthesis gas to methanol (CH₃OH) along with hydrogen (H₂) and water (H₂O). Few noted methods were identifying the optimum recycle purge gas ratio using one-dimensional modelling of process, hydrogenation of carbon dioxide, catalyst deactivation process, and using gas-flowing fixed bed reactor (GFSFBR). These methods have proven to improve the methanol synthesis process.